Ploidy and DNA index as prognostic factors in resected pancreatic ductal adenocarcinoma – a review of the literature - Durlik, Marek; Tuchalska-Czuroń, Julia (Gastroenterology Review/Przegląd Gastroenterologiczny, 2014)
In Poland, pancreatic cancer is the seventh most common cause of cancer-related death amongst men and the sixth amongst women. Pancreatic cancer has an extremely poor prognosis. Radical surgery still remains the only way of curing pancreatic cancer, and this is possible to perform in just 20% of cases, i.e. those that present localised disease upon diagnosis. An average survival of ~20 months post-resection and adjuvant chemotherapy has been observed in 10–15% of patients with tumours limited to the pancreas at the time of presentation. It is necessary to define strong prognostic factors to determine individual treatment and prognosis. In this paper we submit a review of the literature concerning the prognostic impact of the ploidy and the DNA index on the survival of patients who underwent resection of pancreatic ductal adenocarcinoma. However, the presented studies have produced conflicting results. Pancreatic cancer still remains a great challenge in medicine.